The continuous discontinuity of the Greek diaspora in literature or the outsiders of the contemporary Greek literature. - Recuenco-Peñalver, María (My University, 2024)
Greece is traditionally being considered a country of immigrants and this fact has an impact in all aspects of modern life, even in literature. Because of this strong bond that immigrants kept and keep with Greece and, specially, with Greek culture and language, Greek diaspora was considered to be part of a cultural periphery, whose existence complimented Greece beyond its natural borders and helped, among others, to the formation and the understanding of the concept of “nation” during the whole 19th century. Nowadays, the numbers and distribution of Greek diaspora have changed, as well as its importance, but its existence and reality is something that one needs to take into account when we speak about Greek Literature. Otherwise, we would be either forgetting writers like C.P. Cavafy or Stratis Tsirkas —to mention just two authors—, or ignoring the fact that they belonged to the Greek diaspora in Egypt, one of the most important in the whole world, but certainly not the only one. Speaking about contemporary Greek literature and Greek writers, one cannot forget about names like Theodor Callifatides in Sweden, Vassilis Alexakis in France, Olga Broumas or Jeffrey Eugenides in the United States, Panos Karnezis in England or Dadi Sideri in Germany, some of the authors that might not write (only) in Greek, but who convey Greece in their narrative. I shall speak in my paper about how the works of the Greek writers of the modern diaspora are the reflection of this xenitia that exile and migration often cause to them and the importance of writing to get over this feeling.
Keywords: Literatura griega moderna; Grecia - Emigración; Modern Greek; Diaspora; Literature; Self-translation; Exile; Identity